Prospects and Challenges of Embedded Systems for Semiconductor Devices in Industry - A Case Study - Tareq, Abdulla Al; Hossain, Md. Taufiq; Dodaev, Zohar Al; Haque, Abrarul (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this paper is to review the current challenges and prospects of semiconductor devices in Industry. Modern semiconductor devices are not the same without embedded systems, which allow for improved functionality, connectivity, and efficiency in a wide range of industrial applications. This work examines the opportunities and difficulties of integrating embedded systems into semiconductor devices in an industrial setting, concentrating on a thorough case study. This paper investigates the possible advantages of embedded systems, including enhanced performance, lower costs, and more dependability, through a thorough analysis. It also looks at the difficulties that come with its implementation, such as complex designs, interoperability problems, and security risks. The case study offers useful insights into the implementation of embedded systems in semiconductor devices in the real world by emphasizing effective tactics, lessons discovered, and potential future directions. Through the integration of theoretical frameworks and empirical data, this study advances our comprehension of the challenges and opportunities associated with utilizing embedded systems for semiconductor devices in industrial environments. Various functionalities can be included into semiconductor devices thanks to embedded systems, which increases their market potential beyond conventional applications. This creates chances for revenue development and innovation. By improving the adoption and usage of embedded systems, industry practitioners, researchers, and policymakers may boost innovation and competitiveness in the semiconductor sector.